Capable but Excluded: Unpacking the Systemic Barriers to Mathematics Education for Students with Blindness - Tsegaye Gerba Milki; Belay Hagos Hailu; Abebe Yehualawork Male (Nurul Jadid University, 2026)
This study investigates the long-standing exclusion of students with blindness from mathematics education in Ethiopia, despite national commitments to inclusive learning and international frameworks supporting equitable access. Using a qualitative research design, the study gathered data from policymakers, regional education officials, disability advocates, and blind professionals to uncover structural, attitudinal, and pedagogical factors underpinning this exclusion. Data were collected through semi-structured interviews and analyzed thematically to identify patterns across institutional practices and lived experiences. Findings reveal a persistent misalignment between inclusive education policies and their implementation, driven by misconceptions that mathematics is inherently visual, insufficient teacher preparation, and the absence of adapted instructional tools. Testimonies from blind professionals further demonstrate that mathematical competence is attainable when accessible pedagogies are provided, highlighting that exclusion stems from systemic inaction rather than learner limitations. The study concludes that restoring mathematics education for blind learners requires challenging entrenched beliefs, strengthening teacher training, and ensuring institutional accountability. These insights contribute to broader debates on disability-inclusive education and emphasize the need for transformative reforms that honor the educational rights of students with blindness.